Rapid qualitative health research from the Global South: Reflections and learnings from Argentina, Brazil, Chile, and Mexico during the COVID-19 pandemic - Eguiluz, Itzel; Sy, Anahi; Brage, Eugenia; González-Agüero, Marcela (Frontiers in Sociology, 2022)
This work's main objective is to provide insights into our experiences undertaking qualitative rapid research in Latin American contexts from Mexico, Argentina, Brazil, and Chile. We focus on the reflections and learning processes that emerged from our research teamwork during the COVID-19 pandemic. Our research projects are part of an international collaboration led by the Rapid Research Evaluation and Appraisal Lab (RREAL) to explore the experiences of COVID-19 Frontline Healthcare Workers. The analyzed experiences do not only rely on the local work but also on our reflections as a group of Latin American researchers collaborating along with an international team. Qualitative research has an important and long-lasting tradition in Latin America. However, some healthcare professionals are still reluctant to use these methods. We must highlight tensions and dilemmas that have emerged from our own empirical experience: First, the time to gain approval from ethics committees; second, the difficulties in accessing funding to undertake research due to the lack of funding opportunities; third, having to decide the language of our publications. That is just the tip of the iceberg that allows us to show inequalities in scientific knowledge production conditions between the North and the Global South. Following these points, our text explores the tension between the urgency to conduct rapid research and the multiple difficulties when undertaking it during the pandemic, despite the fact those are problems that pre-exist and are magnified during a sanitary emergency. At last, we present the conclusions we arrive at in the reflexive process as a team of women exploring the differences and convergences of our experiences in different countries. That allows us to outline points that help us in the process of doing research and solve obstacles and dilemmas. That winding road we describe here could be an example of other research teams doing research during the pandemic.